Computed tomography pulmonary findings in healthy older adult aspirators versus nonaspirators. (5th August 2013) - Butler, Susan G.; Clark, Hollins; Baginski, Scott G.; Todd, J. Tee; Lintzenich, Catherine; Leng, Xiaoyan
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis In previous studies, we consistently found that approximately 30% of asymptomatic healthy older adults silently aspirated liquids during a flexible endoscopic evaluation of swallowing (FEES) and that their aspiration status was stable for the following year. However, no studies have systematically evaluated effects of silent aspiration on lung parenchyma and airways. We used computed tomography (CT) to compare lungs of healthy older adult aspirators versus nonaspirators. We hypothesized that CT images would show pulmonary differences in healthy older adult aspirators versus nonaspirators. Study Design Prospective study. Methods Fifty healthy older adults (25 aspirators and 25 nonaspirators) who participated in a previous FEES were randomly selected. CT scans were performed; on inspiration, lung views were taken at 1.25 mm and 2.5 mm windows, and on expiration, lung views were taken at 2.5 mm. CT scans were reviewed by radiologists blinded to group assignment. Outcomes included bronchiectasis, bronchiolectasis, bronchial wall thickening, parenchymal band, fibrosis, air trapping, intraluminal airway debris, and tree‐in‐bud pattern. Results χ2 analyses between aspirators and nonaspirators found no statistically significant differences between aspirators and nonaspirators for any outcomes (P > .05). Logistic regression analyses adjusted for smoking did not change the results. Conclusions There were no differences in pulmonary CT findings between healthy older adult aspirators and nonaspirators. This study adds to the evidence that some aspiration may be within the range of normal for older adults, or at least does not contribute to a change in pulmonary appearance on CT images. Level of Evidence 3b Laryngoscope, 124:494–497, 2014